EFFECTS OF HYDROGEN PEROXIDE SOAKING AND NITROGEN FERTILIZER ON THE GROWTH CHARACTERISTICS AND FRUIT YIELD OF FENNEL PLANTS - U. H. Mheidi; H. H. Hasan; M. I. Alhabeeb; M. H. Shenawa (مجلة الأنبار للعلوم الزراعية)
A field experiment was carried out during the winter months of 2018 in the Al-Karma Region of Anbar Governorate, situated at latitude 33º.20.00 north and longitude 44º.24.00 east, to examine the effects of seed soaking in hydrogen peroxide solution and nitrogen fertilization on the growth and yield of fennel plants. Three soaking concentrations were utilized (0, 5, 10 mg L-1), and nitrogen fertilizer was administered at three rates (0, 100, and 200 kg N ha-1). The study employed a factorial experimental design utilizing a randomized complete block design (RCBD) with three replications. The findings indicated a substantial impact on soaking concentrations; the optimal average plant height, branch count per plant, dry weight, inflorescence count per plant, and total yield were observed at a concentration of 10 mg L-1 of hydrogen peroxide. In addition to yield and its components (inflorescence count per plant, weight of 1000 fruits, and total output), elevated nitrogen fertilization at 200 kg N ha-1 enhanced vegetative development characteristics (plant height, number of branches per plant, and dry weight per plant). The interaction among the research components operated comparably to individual factors in their impact on most traits analyzed; nevertheless, it only achieved significance in relation to plant height and the number of inflorescences per plant. In these instances, the interaction treatment with a high concentration of hydrogen peroxide (10 mg L-1) and elevated nitrogen levels (200 kg ha-1) produced the highest averages of 135.64 cm and 165.67 inflorescences per plant, respectively